Detailed anatomical volumetric study of deep nuclei of brain and other structures between parkinson's disease patients who had deep brain stimulation (DBS) and control group - Hwee, Goh Chin (2017)
Background: In my country, Deep Brain stimulation surgery (DBS) was pioneered by Neuroscience team Hospital Universiti Sains Malaysia (HUSM) nearly a decade ago. The treatment was mainly directed to advanced Idiopathic Parkinson’s Disease (PD) patients. Objectives: It is known that volume reduction occurs with age, we searched to define the degree of volume discrepancy in PD patients and attempted to correlate the anatomical volumetric changes to motor symptoms and cognitive function. Methods: The research aimed to establish a baseline Magnetic resonance imaging (MRI) based volumetric analysis of the seven brain structures (Head of caudate nucleus, Putamen, Thalamus, Globus pallidus, Hippocampal head, Amygdala & Subthalamic nucleus) of selected pre-DBS advanced PD patients in comparison to matched healthy controls. Results: Significant atrophy and volume discrepancy were observed in PD surgical group, though thalamus and amygdala were not affected. Positive correlation of globus pallidus volume to higher mental function in the absence of cognitive or behavioural problem. Conclusions: These findings might imply that structural alteration could be the early changes prior to clinical manifestation and PD involves multiple alternative pathway other than nigrostriatal circuit.